2020
DOI: 10.1039/c9fo01996k
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharides from Gracilaria lemaneiformis better attenuated high fat diet-induced metabolic syndrome by promoting the Bacteroidales proliferation

Abstract: Reduction in the degree of polymerization of polysaccharides can improve its bioactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…At the phylum level, the Bacteroidetes were reduced and Firmicutes were increased in WG group, compared with NC group. Although studies have shown that a lower B/F ratio is good for gut health (Xu et al 2020), there have been cases where the opposite results have been found. There is growing consensus that the B/F ratio cannot be used as a biological marker for obesity, diabetes and cardiovascular disease (Magne et al 2020).…”
Section: Discussionmentioning
confidence: 97%
“…At the phylum level, the Bacteroidetes were reduced and Firmicutes were increased in WG group, compared with NC group. Although studies have shown that a lower B/F ratio is good for gut health (Xu et al 2020), there have been cases where the opposite results have been found. There is growing consensus that the B/F ratio cannot be used as a biological marker for obesity, diabetes and cardiovascular disease (Magne et al 2020).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, attenuated metabolic syndrome was related to the increased Bacteroidia ( John et al, 2020 ). The enhanced Bacteroidales were positively correlated with the reduced metabolic syndrome of fat accumulation and lipid disorders ( Xu et al, 2020 ). As a beneficial composition of gut microbiota, the increased richness of Muribaculaceae was an approach for metabolic syndrome alleviation (J.…”
Section: Discussionmentioning
confidence: 99%
“…53 Bacteroidales is an order that comprises closely related members such as Prevotella , Bacteroides and Parabacteroides , and shows beneficial effects in the improvement of obesity. 16 Xu et al 54 showed that the anti-obesity effect of oligosaccharides from Gracilaria lemaneiformis was positively correlated with some members of Bacteroidales. The Clostridium coccoides group was also found to reduce fat content, and increased abundance of the Clostridium coccoides group correlated positively with reduced body weight, BMI and fat mass percentage.…”
Section: Discussionmentioning
confidence: 99%